The hired man question - Wagner, George Franklin (My University, 1899)
Introduction: There is no question at present that is as important to the farmer or even, perhaps, so the country at large, as the question of hired help on the farm. There are many things that could be suggested to improve the conditions as they exist as the present time. The solution of the labor question on the farm is scarcely begun when we think of the system by which labor is handled in other industries. The improvement of farm help would greatly benefit the agricultural industry in general; and in an indirect way this is of vast importance to all other industries, as they are all more or less dependent upon the farm and its products.
Citation: Wagner, George Franklin. The hired man question. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Suggestions for Improvement of Conditions; Salary; Help the Year Round; Treatment of Hand; Theses; Manuscripts (documents)